Storm Eg Agent Profit and Loss Report in February 2022 - Felix Daniel Budiman; Elis Hertini; Julita Nahar (International Journal of Research in Community Services, 2022)
Financial statements are a fundamental thing in a company. One type of financial report is the income statement. The income statement is a report that provides information on the company's performance, which contains income and profit and loss expenses. This study aims to introduce good and simple income statements and understand financial statement analysis. This research uses quantitative methods by using vertical, horizontal and ratio financial analysis techniques. The result of this research is that the Storm egg agent records that the company's finances are in good condition based on the ratio analysis of gross profit margin and net profit margin. Based on the vertical and horizontal analysis, it was found that the company experienced profit growth from the first period to the second period.